Gypensapogenin I alleviates PANoptosis, ferroptosis, and oxidative stress in myocardial ischemic–reperfusion injury by targeting the NOX2/AMPK pathway - Chen, Yuqiong; Guan, Bo; Lu, Jian; Yan, Xiaopei; Huang, Chao; Qiu, Yuli; Li, Xinyan; Sun, Xiangyu; Chen, Lin; Li, Wei; Mao, Wenjun; Sun, Zhongqi; et al. (Frontiers in Cell and Developmental Biology, 2025)
AimThis study aims to investigate the benefits of gypensapogenin I (GI) on myocardial ischemia–reperfusion injury (MIRI) and the underlying mechanisms.MethodsAn MIRI model was established by ligating the anterior descending coronary artery (LAD) followed by blood flow restoration in mice. Cardiac dysfunction and myocardial infarction size were evaluated by echocardiography and triphenyltetrazolium chloride (TTC) staining. PANoptosis, ferroptosis, and mitochondrial redox state were examined by immunofluorescence, Western blotting, and an ELISA kit. In addition, molecular and biochemical methods were applied to illustrate the exact mechanisms of GI on MIRI.ResultsGI pretreatment alleviated cellular oxidative stress, inhibited PANoptosis and ferroptosis, reduced myocardial infarction area, and improved cardiac function during MIRI. Further results revealed that mitochondrial biogenesis and the anti-oxidative system were impaired in mice suffering from MIRI, and these effects were significantly alleviated by GI treatment via downregulation of the NADPH oxidase 2 (NOX2) level. Moreover, NOX2 promoted mitochondrial dysfunction by suppressing the AMP-activated protein kinase (AMPK)–PGC-1α–Sirt3 signaling pathway. In addition, the NOX2 activator exacerbated oxidative damage and offset all the beneficial effects of GI on mitochondrial function, PANoptosis, and ferroptosis. Meanwhile, reinforced AMPK phosphorylation by GI or AMPK activator (5-aminoimidazole-4-carboxamide ribonucleotide, AICAR) maintained the mitochondrial redox state and biogenesis and suppressed PANoptosis and ferroptosis.ConclusionGI pretreatment protected the cardiomyocytes from MIRI-induced PANoptosis and ferroptosis by maintaining the mitochondrial redox state and biogenesis through the modulation of the NOX2/AMPK signaling pathway. Our findings indicate that GI pretreatment could be a promising therapeutic agent for MIRI treatment.